Impact of using excellence management models is the customer Satisfaction of Brazilian electricity distributors – 10 years of studies - Carrasco, A.; Andrade, M. A. P.; Rosa, A. (WSMC13 – 13th International Conference on Statistics, Mathematics and Computation, 2019)
The article evaluates the impact of the use of the model of excellence in Brazilian management (MEG) by electricity distribution companies and their impact on customer satisfaction (IASC). It was evaluated 10 years of use of the model in groups of companies with different levels of implantation of the model (users, indifferent, engaged and winning) using statistical methods. As results it is verified the existence of differences between the groups revealing the correct decision by the use of the model seen by this view. The results can be used by similar organizations or other industries Its importance is reinforced by the coverage of studies that reaches 96% of the sector, for a decade (2007 to 2016), by the use of publicly unavailable sources. The organizations were classified according to the use of the MEG (Excellence in Management Model) and evaluated, through statistical tests, differences between the indicators in these groups, allowing to conclude about the mass adoption of the MEG and impacts on the non-financial indicators more relevant in this sector.